Critical thinking for a pluralistic univerity - Wolrath Söderberg, Maria (Šolsko polje, 2007)
Fostering critical thinking is usually seen as one of the most important responsibilities of university education. Surveys of the Swedish Board of Education show this to be a complicated task. Our own investigations indicate that the dominant view of critical thinking is logical-deductive. We are convinced that this narrow understanding of critical thinking is insufficient for our contemporary pluralistic university, requiring interdisciplinary co-operations and gradually including more heterogeneous, perhaps multicultural student groups. Within the framework of the project "Critical Thinking for a Pluralistic University" we want to develop alternative conceptions of critical thinking. Particularly we conceive of critical thinking as a way of handling many concurring perspectives. In this paper we would like to discuss if and how traditions like classical sophistry, rhetorical renaissance pedagogy, modern hermeneutical theories and critical theory can contribute to a more comprehensive pedagogy of critical thinking adapted to modern requirements.
Keywords: argumentacija; debata; kritično mišljenje; retorika; učenje; univerze